Behind Closed Doors: The Priorities of the Alcohol Industry as Communicated in a Trade Magazine - Pettigrew, Simone; Hafekost, Claire; Jongenelis, Michelle; Pierce, Hannah; Chikritzhs, Tanya; Stafford, Julia (Frontiers in Public Health, 2018)
Background: Efforts to reduce alcohol-related harm face strong resistance from the alcohol industry. It is important to monitor industry actions over time to assist in developing appropriate responses to this resistance. Monitoring can enable public health to identify industry positions on alcohol policy issues, stay abreast of current and emerging marketing tactics, and inform the development of possible counter-actions. One form of monitoring is the examination of industry trade publications where the industry converses with itself. The aim of this study was to assess industry strategic approaches as communicated in articles published in a leading Australian alcohol trade magazine to provide insights for policy makers and advocacy groups. Methods: Thematic analysis of 362 articles published in a trade magazine over a one-year period. Results: Three primary themes were evident in the articles: (1) the legitimization of alcohol as an important social and economic product, (2) the portrayal of the industry as trustworthy and benign, and (3) the strategic embedding of alcohol in various facets of everyday life. Conclusions: There was a general failure to acknowledge the substantial burden of disease caused by alcohol products, and instead much effort was expended on legitimizing the product and the companies responsible for its production, distribution, and promotion. The level of denial exhibited shows that additional regulation of the industry and its tactics will need to proceed without industry acceptance. Clear resistance to increasing consumer protections also points to the futility of inviting industry members to the policy table.